Effects of residual pectin composition and content on the properties of cellulose nanofibrils from ramie fibers. (15th December 2022) - Yu, Wang; Yi, Yongjian; Wang, Hongying; Yang, Yuanru; Xing, Chen; Zeng, Liangbin; Tang, Juntao; Tan, Zhijian
Abstract: In this study, a series of pretreatment methods (pectin extraction) were employed to prepare cellulose nanofibrils (CNFs) with different pectin composition and contents from ramie fibers. The comprehensive effects of residual pectin on the final properties of CNFs were investigated. The residual pectin did not have a significant effect on the size distribution of the obtained CNFs. While the presence of pectin led to higher zeta potential value, improved dispersion stability and enhanced storage modulus of the CNF dispersion, with the sodium carbonate extraction method showing the greatest impact. The possible mechanism for enhanced dispersion stability of CNFs is the formation of self-assembled hierarchical pectin-hemicellulose/lignin-cellulose nanostructures, offering abundant electrostatic repulsion and steric hindrance between the nanoparticles. This work provides guidelines for the tailored production of CNFs to meet the requirements for different applications. Graphical abstract: Unlabelled Image